Internet Of Things (IoT) In Water Quality Monitoring Systems And Nutrition In Hydroponic Plants - Irawati Irawati; Diar Irmawati; M. Ganda Arya Permana; Mohamad Riziq Amri (Eduvest - Journal of Universal Studies, 2021)
Abstract Population is growing every year. This has an impact on the reduction of agricultural land to cultivate crops. This study aims to combine a concept that aims to expand the benefits of continuously connected internet connectivity. Based on the long term, the narrowing of agricultural land will have an impact on the scarcity of hydroponic NFT (Nutrient Film Technique) is a model of cultivation by putting the roots of plants in a shallow layer of water. The water is circulated and contains nutrients according to the needs of plants. This study combines hydroponic plants with the help of Internet of Things (IoT) technology using hydroponic planting techniques. Rooting can develop in a nutrient solution, because around rooting there is a layer of nutrient solution then the system is known as NFT. Excess water reduces the amount of oxygen and dissolved nutrients. The use of a manual measuring instrument is actually time-consuming if the owner is busy. Based on this background, the author got the idea to create a system of monitoring water quality and nutrients in hydroponic plants that can be accessed through a mobile phone.